Navigating Frontal Lobe Arteriovenous Malformation Resection: A Case Report on TIVA with Propofol-Remifentanil TCI for Hemodynamic Stability and ICP Control - I Gede Catur Wira Natanagara; I Putu Pramana Suarjaya; Ida Bagus Krisna Jaya Sutawan (HM Publisher, 2025)
Background: Arteriovenous malformations (AVMs) located within the frontal lobe present considerable anesthetic challenges. These challenges arise from the critical functions governed by this brain region and the inherent risks associated with intracranial surgery, notably hemodynamic instability and the potential for elevated intracranial pressure (ICP). The utilization of Total Intravenous Anesthesia (TIVA) through Target-Controlled Infusion (TCI) systems for propofol and remifentanil provides a sophisticated strategy for achieving precise control over anesthetic depth and maintaining physiological homeostasis. This report offers a detailed account of such a case. Case presentation: A 25-year-old male patient, classified as ASA III, presented with a right frontal lobe Spetzler-Martin Grade I AVM and was scheduled for elective microsurgical resection. The anesthetic management centered on a TIVA approach, employing propofol administered via an Eleveld TCI model (target concentration range: 2-5 µg/mL) and remifentanil via a Minto TCI model (target concentration range: 4-6 ng/mL). Comprehensive intraoperative monitoring included invasive arterial blood pressure and central venous pressure. Pharmacological adjuncts included mannitol, dexamethasone, and tranexamic acid. Throughout the procedure, stable intraoperative hemodynamics (target Mean Arterial Pressure [MAP] 70-90 mmHg) were successfully maintained, and intracranial pressure was effectively controlled, thereby facilitating the complete AVM resection. The patient was extubated in the post-operative period, demonstrated a stable neurological status, and was subsequently managed in the Intensive Care Unit (ICU). Conclusion: A meticulously planned and executed TIVA-TCI regimen, featuring propofol and remifentanil, when integrated with thorough invasive monitoring and proactive pharmacological interventions, demonstrated effectiveness in preserving crucial hemodynamic stability and fostering optimal intracranial conditions. This comprehensive anesthetic strategy was instrumental in the successful surgical resection of a frontal lobe AVM and contributed to a favorable neurological outcome for the patient.